Biodiversity hotspot in the Sangha Trinational Protected Area revealed through Orthoptera Tettigoniidae - Massa, Bruno (Zootaxa, 2023)
This paper deals with the study of the Orthoptera Tettigoniidae found in Nouabalé-Ndoki National Park (Republic of Congo) and the comparison of the results with those previously found in the neighbouring Dzanga-Ndoki National Park (Central African Republic). The study of specimens allowed for the description of a new tribe Myllocentrini, a new genus Pseudoeurycorypha (type species: P. civilettorum n. sp. from Republic of Congo, Central African Republic, and Côte d’Ivoire), and six new species Plangiopsis nouabalensis, Leiodontocercus vicentae, Phlaurocentrum dentatum, Poreuomena derozierae, Tetraconcha maculosa and Tetraconcha laszloi from Republic of Congo. In addition, Phlaurocentrum morettanum n. sp. is described from Côte d’Ivoire, while Phlaurocentrum morettoi Massa, 2013 from Central African Republic is synonymized with P. lobatum Ragge, 1962 from Democratic Republic of Congo. Furthermore, morphological evidence allows for the inclusion of three genera, Bongeia Sjöstedt, 1902, Itokiia Sjöstedt, 1902, and Tapiena Bolívar, 1906 (presently Afrotapiena n. gen.; species type: Tapiena minor Bolívar, 1906 from Ghana), in the tribe Plangiopsidini Cadeña-Castaneda, 2015 which currently contains Plangiopsis Karsch, 1889 and Plangiola Bolívar, 1906. Moreover, new morphological data on the group of Arantia rectifolia Brunner von Wattenwyl, 1878, including Arantia tanzanica Hemp & Massa, 2017 and Arantia marginata Massa, 2021, has enabled these two species to be transferred from the subgenus Euarantia Heller, 2014 to Arantia Stål, 1874. The male of Anthracopsis gigliotosi Karny, 1907 is described, and other species of Tettigoniidae are reported for the first time from Republic of Congo. Most of the endemic species or genera are highly vulnerable to extinction due to their small distributional ranges. The results highlight the importance of the Congo River Basin as a biodiversity hotspot and underline the need to find appropriate, additional and urgent conservation measures for this area of tropical forest.